Treatment modalities for hyperpigmented skin lesions: A brief overview - Yan, Teng Khoo; Halim, Ahmad Sukari (PiscoMed Publishing, 2016)
Skin hyperpigmentation involves a broad range of skin conditions, including epidermal pigmented lesions, dermal pigmented lesions, and mixed pigmented lesions. Treatment includes various modalities such as brightening cream, chemical peeling, and laser therapy. Responses to various treatment modalities can be quite varied depending on the type of treatment and the degree of pigmentation. Sometimes a lesion can lighten or even partially disappear, while other lesions may recur. This paper provides a brief overview of treatment modalities available for hyperpigmented skin lesions including the importance of photoprotection, various types of brightening creams, suitable types of chemical peels, specific laser therapies targeted for skin hyperpigmentation, and surgery.